Pelatihan Desain Grafis Bagi Santri Pondok Pesantren Pabelan - Danang Tejo Kumoro; Uswatun Hasanah; Valian Yoga Pudya Ardhana (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Pondok Pesantren Pabelan is an Islamic school, located in the village of Pabelan, Mungkid, Magelang, Central Java. Pondok Pesantren Pabelan teaches various skills for students. One of the skills that are being held is graphic design but it is constrained by the trainer who is not yet available so that the implementation has been limited to the efforts of each student in learning. This training program aims to meet students' knowledge and skills needs in the field of graphic design so that in the future students can use it for their needs and be implemented into the activities and needs of the pesantren. The activity begins with an introduction and briefing on the definition and use of graphic design in various aspects, followed by technical material then direct practice using graphic processing applications. In the final section, an evaluation is carried out to measure the level of practical ability of the students in using equipment and designing according to the provisions of the trainer, using variables of similarity in shape, dimensions, and layout.